Headache and sleep quality in mitochondrial diseases - Alejandro Herrero San Martin; Cristina Dominguez Gonzalez; Montserrat Morales Conejo; Maria Elena Hernández Salas; Jesús Hernández Gallego (SAGE Publishing, 2023)
Objective: Describe the characteristics and prevalence of headache in patients with mitochondrial diseases (MDs), as well as sleep quality, trying to observe possible associations. To assess whether these patients are more likely to suffer headaches in relation to poorer quality of sleep. Background: Sleep disorders and headache are considered to be common in MDs. We present the largest sample analyzed to date. Methods: Observational, descriptive, cross-sectional study that analyzed a database of 232 patients with MDs, including age, sex, genotype, phenotype, presence and characteristics of headache. All patients fulfilled the Epworth Sleepiness Scale (ESS), the Pittsburgh Sleep Quality Index (PSQI) and, in migraine, the Migraine Disability Assessment questionnaire (MIDAS). Headache was divided into two groups: migraine headache, according to criteria of the International Classification of Headache Disorders (ICHD-III beta), and non-migraine headache. Results: A total of 203 cases were analyzed, 124 women (61%) and 79 men (39%). Average age was 46 years. Most frequent DNA mutation was m.3243 A > G in MITL1 gene (33%). Most frequent phenotype was MELAS syndrome: 28 patients (13.8%). Ninety-two patients (45.3%), reported headache, 44 fulfilling migraine criteria (21.7%). Headache was more frequent in MELAS syndrome ( p < 0.01). Statistically significant differences were found in the number of disabling episodes per month in patients with migraine ( p < 0.001). Patients with headache scored higher in Epworth ( p = 0.01) and Pittsburgh scales ( p < 0.001). Conclusions: A higher prevalence of migraine is observed in patients with mitochondrial diseases, independent of genotype and phenotype. MD-associated migraine tends to be chronic and more disabling. A higher frequency of headache, not specifically migraine, has also been observed in patients with MELAS syndrome. Mitochondrial dysfunction could be one of the pathophysiological mechanisms of migraine and a factor of chronification and severity. Poor sleep quality could also be associated with headache in patients with MDs. Assessment of headache and sleep disturbances should be part of the routine workup of patients with mitochondrial disease. Trial registration: N/A.